Development of a Problem Based Learning Science E-Module Integrating Ledre Local Wisdom to Foster Junior High School Students' Critical Thinking Skills - Nofal Binti Ali Mahfud; Sifak Indana; Isnawati (Yayasan Darussalam Bengkulu, 2026)
This study aimed to develop and evaluate a Problem-Based Learning (PBL)-based science e-module integrating the local wisdom of Ledre to foster junior high school students' critical thinking skills on the topic of food additives. The study employed a Research and Development (R&D) approach using the 4D model consisting of the Define, Design, Develop, and Disseminate stages. The developed product was evaluated in terms of its validity, practicality, and effectiveness. Product validity was assessed by subject-matter experts, instructional media experts, and science education practitioners using Aiken's V. Practicality was evaluated through learning implementation observations, teacher and student response questionnaires, and readability analysis. Effectiveness was determined using a one-group pretest-posttest design involving 64 eighth-grade students from two classes receiving the same instructional treatment. Students' critical thinking skills were analyzed using the Normalized Gain (N-Gain) and the Wilcoxon Signed-Rank Test. The developed science e-module achieved an average Aiken's V coefficient of 0.93, indicating high validity, while the assessment instrument demonstrated good reliability (Cronbach's Alpha = 0.815). Practicality evaluation showed highly positive implementation and user responses, indicating that the e-module was feasible for classroom application. Students' critical thinking skills improved from a mean pretest score of 43.55 to a mean posttest score of 83.73, with an average N-Gain score of 0.6965 (moderate category). The Wilcoxon Signed-Rank Test confirmed a statistically significant improvement (p < 0.001), accompanied by a very large effect size (r = 0.87). These findings demonstrate that integrating Ledre local wisdom into the Problem-Based Learning framework provides an effective digital learning resource for fostering contextual science learning and enhancing junior high school students' critical thinking skills.